2020
DOI: 10.1096/fj.202000245r
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamins and lysophospholipids are critical for inducing mouse spermatogenesis under organ culture conditions

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…These substances were effective in mouse IVS, too. We found in our previous studies that hormones, antioxidants, and lysophospholipids examined in this study had a definite effect on improving IVS in mice 21 , 22 . Thus, their effects are not specific to rats, but are common to mice as well.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…These substances were effective in mouse IVS, too. We found in our previous studies that hormones, antioxidants, and lysophospholipids examined in this study had a definite effect on improving IVS in mice 21 , 22 . Thus, their effects are not specific to rats, but are common to mice as well.…”
Section: Discussionsupporting
confidence: 56%
“…In our previous study, lysophosoplipids was shown to be effective in inducing/promoting mouse IVS 22 . So, we investigated if the lysophopholipids are effective to rat IVS as well.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Lipids are critical components in spermatogenesis. For example, albumin-bound lipids such as lysophospholipids are critical for inducing mouse spermatogenesis even under organ culture conditions 17 . Phospholipids containing PUFAs, especially DHA, are important for the formation and function of sperm 18 20 .…”
Section: Discussionmentioning
confidence: 99%